Our Folktales : The All-Time Favourite Folktales of Asia / The All-Time Favourite Folktales of Asia - Wan, Ruth, 1976- (Singapore : WS Education, 2021)
Our Folktales: The All-time Favourite Folktales from Asia is a collection of eight beloved children's stories from China, India, Indonesia, Japan, Malaysia, Myanmar, Philippines and Singapore.
Keywords: Tales -- Asia; Folklore -- Asia; Folklore